Numerical data for the paper "Vector dark matter production during inflation in the gradient-expansion formalism" - Lysenko, Anastasia; Sobol, Oleksandr; Vilchinskii, Stanislav (My University, 2026)
Data files containing numerical results illustrating the fundings of the paper "Vector dark matter production during inflation in the gradient-expansion formalism" https://arxiv.org/abs/2509.24963